2016
DOI: 10.3389/fpls.2016.01179
|View full text |Cite
|
Sign up to set email alerts
|

A Different Pattern of Production and Scavenging of Reactive Oxygen Species in Halophytic Eutrema salsugineum (Thellungiella salsuginea) Plants in Comparison to Arabidopsis thaliana and Its Relation to Salt Stress Signaling

Abstract: Isolated thylakoids from halophytic Eutrema salsugineum (Thellungiella salsuginea) produces more H2O2 in comparison to glycophytic Arabidopsis thaliana. The first objective of this study was to verify whether this feature is relevant also to the intact chloroplasts and leaves. Enhanced H2O2 levels in chloroplasts and leaves of E. salsugineum were positively verified with several methods (electron microscopy, staining with Amplex Red and with diaminobenzidine). This effect was associated with a decreased ratio … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 58 publications
2
30
0
Order By: Relevance
“…Oxidative stress is known to induce thylakoid swelling (e.g. Yamane et al 2012;Gao et al 2015;Meng et al 2016;Pilarska et al 2016) as seen in the p39 mutants (Fig. 3).…”
Section: Discussionmentioning
confidence: 93%
“…Oxidative stress is known to induce thylakoid swelling (e.g. Yamane et al 2012;Gao et al 2015;Meng et al 2016;Pilarska et al 2016) as seen in the p39 mutants (Fig. 3).…”
Section: Discussionmentioning
confidence: 93%
“…These findings led the authors to speculate that enhanced leakage of H 2 O 2 from E. salsugineum plastids preadapts the halophyte to salt stress by maintaining an up-regulated antioxidant system while preventing ROS damage. This hypothesis is further supported by the following observations: (1) the reduced activity of H 2 O 2 -detoxifying enzymes, such as ascorbate peroxidase (APX) in E. salsugineum and similar activities of catalase in E. salsugineum and Arabidopsis (Pilarska et al, 2016); and (2) the ability of E. salsugineum to sustain a highly reduced plastoquinone pool (Wiciarz et al, 2015(Wiciarz et al, , 2018. This could facilitate the persistence of the cellular H 2 O 2 signal (Bose et al, 2014).…”
Section: Halophytic Photosynthetic Performance and Protective Antioximentioning
confidence: 94%
“…A similar amount of H 2 O 2 production is induced in Arabidopsis and E. salsugineum leaves a few hours after a 400 mm NaCl shock treatment, whereas higher induction of H 2 O 2 is observed in E. salsugineum roots (Ellouzi et al, 2014). However, a more detailed analysis using plants adapted to milder saline conditions (150 mm for Arabidopsis and 300 mm for E. salsugineum), employing a variety of complementary methods, demonstrated that both isolated thylakoid membranes and chloroplasts from intact E. salsugineum leaf tissue produce more H 2 O 2 in both control and saline conditions compared with Arabidopsis (Pilarska et al, 2016). Furthermore, under control conditions, a lower amount of damaging superoxide is generated in E. salsugineum than in Arabidopsis, which is correlated with reduced lipid peroxidation in isolated thylakoids and intact leaves of the halophyte.…”
Section: Halophytic Photosynthetic Performance and Protective Antioximentioning
confidence: 99%
“…Eutrema salsugineum (formerly Thellungiella halophila ) is a model species for the study of plant stress tolerance (Amtmann, 2009; Bressan et al, 2001; Griffith et al, 2007; Oh et al, 2010; Orsini et al, 2010; Pilarska et al, 2016; Taji et al, 2004; Volkov et al, 2003; Wong et al, 2005). The two most commonly studied accessions, Shandong (SH) and Yukon (YK), are native to the Yellow River region of China (Bressan et al, 2001; Inan et al, 2004) and the Yukon territories of Canada (Wong et al, 2005), respectively.…”
Section: Introductionmentioning
confidence: 99%